Knowledge and attitudes towards smoking cessation counselling: an Italian cross-sectional survey on tertiary care nursing staff - Laura Maniscalco; Salvatore Barretta; Giuseppe Pizzo; Domenica Matranga (PeerJ, 2021)
Background One of the most effective smoking cessation strategies involves care and advice from nurses due to their role in the front line of treatment. Lack of education on smoking cessation counselling may be detrimental, and adequate smoking cessation training during healthcare studies is needed. Objectives The study aimed to examine nurses’ attitudes, belief, and knowledge of smoking cessation counselling; knowledge of the health risks associated with smoking was also assessed. Design A cross-sectional survey on 77 nurses from the nursing staff of Cardiology, Cardiac Intensive Care and Surgical Oncology Units of two tertiary hospitals. Methods Cronbach’s alpha was calculated to assess the questionnaire’s internal consistency, and three composite indicators were computed to assess the three dimensions of the questionnaire (knowledge, attitude, belief). Furthermore, a stepwise linear regression model was used to predict the attitude to be engaged in smoking cessation counselling, related to demographic and behavioural variables, as well as knowledge and belief indicators. The analysis was stratified by Unit. Results Nurses from three Units had a significantly different attitude score (2.55 ± 0.93 for Cardiology, 2.49 ± 0.72 for Cardiac Intensive Care and 2.09 ± 0.59 for Surgical Oncology Unit) (P-value = 0.0493). Analogously, knowledge of smoking cessation counselling was reported to be higher for Cardiac Intensive Care Unit nurses (3.19 ± 0.70) compared to Surgical Oncology nurses (2.73 ± 0.74) (P-value = 0.021). At the multivariable analysis, attitude towards smoking cessation counselling was significantly related to the nurse’s belief about counselling, for Cardiology staff (coeff = 0.74, 95% CI [0.32–1.16], P-value = 0.002) and for Surgical Oncology staff (coeff = 0.37, 95% CI [0.01–0.72], P-value = 0.042). Conclusions Incorporation of smoking cessation interventions in nurses’ and nursing managers’ education could improve the nursing staff’s attitude, belief, and knowledge regarding smoking cessation counselling, which would lead to the inclusion of tobacco prevention and cessation as an integral part of patient care.